Immunophenotyping pancreatic cystic lesions for cancer risk stratification - Lyons, Rebecca (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2026)
Pancreatic cancer (PC) remains one of the most lethal malignancies worldwide, with a five-year survival rate of approximately 13%. This poor prognosis stems largely from the aggressive and asymptomatic nature of the disease which frequently results in late-stage clinical presentation. PC is generally poorly responsive to standard-of-care therapies, with patients achieving little to no improvements in overall survival, particularly due to the development of treatment resistance. One promising avenue for early detection and prevention of PC lies in the study of pancreatic cystic lesions (PCLs). PCLs are fluid-filled structures found within or on the surface of the pancreas. While many PCLs are benign, others such as intraductal papillary mucinous neoplasms (IPMNs) or mucinous cystic neoplasms (MCNs), possess the ability to undergo malignant transformation and can be regarded as precursor lesions of PC. The immune landscape of pre-malignant PCLs and its role in determining malignant potential remain poorly understood. Given that PC is typically considered an "immunologically cold" tumour, understanding the mechanisms involved in cystogenesis and tumourigenesis may be the key to identifying novel immune biomarkers within pre-malignant PCLs to further define existing stratification frameworks and provide high-risk patients with the appropriate surveillance and timely intervention. This investigative approach may also provide avenues of earlier PC diagnosis and intervention. Therefore, this study aims to 1) characterise the immune cell infiltrate and immunomodulatory secretome of risk-stratified PCL cyst fluid for improved cancer risk stratification, 2) investigate the influence of the soluble immunomodulatory secretome of risk-stratified pancreatic cyst fluid (PCF) on anti-tumour effector cell function and 3) elucidate key chemokine profiles in risk-stratified PCF to identify potential chemokine-based therapeutic targets that may enhance effector immune cell infiltration into the tumour microenvironment (TME). This thesis aimed to characterise the local and systemic immune microenvironment of pre-malignant PCLs and to identify immune-related biomarkers and therapeutic targets associated with progression risk. Immunophenotyping was performed by flow cytometry on the immune cell infiltrate of PCF and patient-matched peripheral blood mononuclear cells (PBMCs). In parallel, the soluble immune microenvironment of PCLs was profiled using multiplex enzyme-linked immunosorbent assay (ELISA) platforms to quantify the expression of immunomodulatory mediators including cytokines, chemokines, growth factors, and adhesion molecules in risk-stratified PCF. Finally, co-culture assays and lymphocyte killing assays were employed to assess the impact of PCF from benign pseudocysts, low-risk PCLs, and high-risk PCLs on effector immune cell phenotype and function. Data from this study revealed that adaptive immune cell populations, including CD4+ T cells, CD8+ T cells, and natural killer (NK) cells, predominantly compose the immune cell infiltrate of pre-malignant PCF. However, these effector immune cells exhibited features of functional exhaustion, suggesting early immune dysfunction within the cyst microenvironment. Lymphocyte killing assays demonstrated that benign and low-risk PCF enhanced lymphocyte-mediated cytotoxicity against PC cells whereas high-risk PCF failed to do so, implying progressive immune silencing with disease progression. Furthermore, low-risk PCF was found to have an immune-active phenotype, characterised by abundant soluble cytokines, growth factors, and chemotactic factors, while high-risk PCLs exhibited diminished immune activity, consistent with the emergence of an immunosuppressive phenotype. Additionally, migration of T cells and NK cells was significantly increased towards PCF from patients with a low risk of PC development, a finding not observed with high-risk PCF or benign pseudocyst fluid. Collectively, these findings support a model in which immune-active low-risk lesions evolve into high-risk states over time, losing their immune-active phenotype and enabling malignant transformation. In conclusion, findings from this thesis advance the current understanding of immune dysregulation in the pre-malignant PCL setting and highlights the potential of immune-based biomarkers for cancer risk stratification in patients with PCLs. By defining key immunological alterations associated with PCL progression, this study provides a rationale for early immunomodulatory intervention aimed at maintaining immune surveillance and preventing malignant progression.
APPROVED
Keywords: Pre-malignant pancreatic cystic lesions; Pancreatic cancer; Cancer risk stratification; Immune-based biomarkers; Early intervention